The Development of Biology Module Based on Local Wisdom of West Lampung: Study of Ecosystem Material. (February 2020) - Haka, N B; Anggoro, B S; Hamid, A; Novitasari, A; Handoko, A; Puspita, L
Abstract: Education has a mission to develop the potential of students, develop their personality, and be able to foster a sense of responsibility. For this reason, teaching materials are needed. Module teaching materials based on local wisdom on ecosystem materials are not yet available as Teaching materials used by schools. For this reason, it was necessary to develop module teaching materials based on local wisdom in supporting the achievement of competencies and learning objectives. This study aimed to determine the development, feasibility and response of students and educators towards the Biology module based on local wisdom in West Lampung. This study used Research & Development (R&D) method with Borg & Gall procedure. Data collection techniques were using expert questionnaires (teaching modules, materials, languages), response questionnaires (students and educators), and documentation. Riduwan modified Likert scale research data analysis techniques were used. The results showed the module was suitable for using in the learning process based on the module quality assessment by experts (teaching modules, material, and language) with overall criteria very feasible. Biology educator's response was very positive towards the teaching module products. It could be concluded that the module is suitable for use in the biology learning process.